Economic Literacy In Developing Countries: A Literature Review Of Educational Strategies, Socioeconomic Outcomes, And Policy Challenges - mahmud ismail; Lailatul Rohmah (International Journal of Economics, Science, and Education, 2026)
Purpose: This study aims to examine the development of economic literacy research in developing countries by analyzing educational strategies, socioeconomic outcomes, and policy challenges that influence individuals' economic knowledge and decision-making capabilities. The study seeks to provide a comprehensive understanding of how economic literacy contributes to human capital development, financial well-being, and sustainable socioeconomic progress. Design/methodology/approach: This study employs a qualitative approach using a literature review method. Relevant articles, policy reports, and scholarly publications on economic literacy in developing countries were systematically reviewed to identify major themes, educational approaches, socioeconomic impacts, and policy issues. The analysis integrates perspectives from human capital theory and educational development frameworks. Findings: The review reveals that economic literacy plays a significant role in improving financial decision-making, entrepreneurial capacity, resource management, and household welfare. Educational interventions through formal education, community-based learning, and digital platforms have contributed positively to economic understanding among individuals. However, disparities in educational access, socioeconomic conditions, digital infrastructure, and policy implementation continue to hinder the development of economic literacy in many developing countries. Research limitations/implications: This study is limited to secondary data and published literature. Future research should employ empirical approaches to examine the effectiveness of specific economic literacy programs across different demographic and regional contexts. Practical implications: The findings provide insights for policymakers, educators, and development practitioners in designing more inclusive economic literacy programs, strengthening curriculum development, and enhancing public awareness initiatives to support sustainable economic development. Originality/value: This study contributes to the literature by offering a comprehensive synthesis of economic literacy research in developing countries while highlighting key educational strategies, socioeconomic benefits, and policy challenges that require further scholarly and practical attention. Paper type: Literature review